PEMBATASAN ENERGI RANSUM PADA SAPI BALI YANG DIBERI PELEPAH SAWIT PADA LEVEL BERBEDA TERHADAP KOMPOSISI TUBUH - DIANA DELVIA NANDA; AGUNG PURNOMOADI; LIMBANG KUSTIAWAN NUSWANTARA (Jurnal Peternakan, 2013)
Nowadays the livestock industries are required to produce a low-fat meat, because fat has a negative effect on the healthof consumers. Efforts to address the accumulation of fat is done by energy restriction in animal feed. If the feed does not meetthe needs of energy, then these requirements will be met by dismantling the body fat stores. Feed given to cows intended toproduce maximum production performance. The productivity of an animal to be seen apart from the weight gain, it can alsobe reflected by the composition of body components. One way to look at the composition of the animal body components withurea space techniques. The aim of this research was to determine the potency of palm frond as a grass field alternative to balicattle diet. The experimental design used was a randomized complete block design consisted of 4 treatments and 4replications. Feed treatments were : A = 60% field grass + 40% palm cake, B = 40% field grass and 20% palm frond + 40%palm cake, C = 20% field grass and 40% palm frond + 40% palm cake, D = 60% palm frond + 40% palm cake. The resultsshowed that the use of palm frond various levels did not significantly (P>0,05) affect the value of the body composition.Average water body on treatment A, B, C and D were 51.15%, 51.24%, 50.61% and 50.85%, respectively. An average bodyprotein on treatment A, B, C and D were 13.22%, 13.23%; 13.0% and 13.15%, respectively. Average body fat in treatmentA, B, C and D were 30.49 %, 30.37 , 31.19 and 30.88 %, respectively. This study demonstrated that administration palmfrond could be used as grass field alternative to cattle diet.